REINFORCEMENT OF THE SUBGRADE AS THE WAY OF IT WORKS IN THE STAGE OF ELASTIC DEFORMATION - Buhaiev, O. K.; Tsepak, S. V.; Tiutkin, O. L. (Science and Transport Progress, 2004)
The work represents the fundamentals of ground bed reinforced technology, as a mode of its work at resilient stage. Examples for its realisation are provided. The necessity of improvement of reinforcement methods has been substantiated; recommendations for application of its alternative kinds have been developed.